Water (in)security in Gafsa, Tunisia: A hydrosocial approach - Chloé Nicolas-Artero; Fatma Karaouli; Latifa Dhaouadi; Zaineb Ali; Nadia Khelif; Mongi Ben Zaied; Mohamed Ouessar; Elena Bresci; Maria Cristina Rulli (Agricultural Water Management, 2025)
The drylands of Global South countries offer significant potential for agricultural development, often at the expense of the sustainability of groundwater resources. This article complements quantitative approaches by adopting a hydrosocial perspective to highlight the power and economic relationships that affect water distribution. This study, centred on the Gafsa region of Tunisia, explores the nexus between intensive agriculture and water scarcity. It delves into the political and personal measures adopted to address the challenges posed by limited water access. The analysis reveals that the modernisation of agriculture, spearheaded by external investors, has led to the escalation of irrigation practices, ractices, resulting in a surge in water demand and depletion of groundwater reserves. Wealthier farmers and investors have exacerbated socioeconomic disparities by adapting more effectively to water shortages, further marginalising small-scale farmers. To address this issue, the government introduced regulations limiting the extraction of groundwater and promoting alternative water sources. However, these measures have not been successful, as the state has allowed illegal water extraction to maintain social stability. This research sheds light on the ambiguity of Tunisia’s agricultural development strategy and the contradictions in its water policy. The Gafsa case study offers insights into the global challenges of intensive agriculture in water-scarce regions. Recommendations include the need for a more inclusive water management framework that integrates the voices and needs of smallholder farmers.